Psychometric evaluation of medication safety competence scale for clinical nurses - Zhen Yang; Fengmin Chen; Yingying Lu; Huijun Zhang (BMC Nursing, 2021)
Abstract Background Nurses are the most important members of the health care system for medication safety, there are few tools to evaluate their medication safety competence. This study aimed to translate the Medication Safety Competence Scale into Chinese and validate its reliability and validity among clinical nurses. Methods A total of 894 clinical nurses were recruited from three cities in China. The original version of the Medication Safety Competence Scale was translated into Chinese using the backward and forward translation procedure. The reliability of the scale was measured by internal consistency, split-half reliability, and stability. The validity of the scale was assessed by the content validity index, exploratory factor analysis and confirmatory factor analysis. Results The Cronbach’s coefficient of the scale was 0.940, and the coefficient values for the six domains ranged between 0.843 and 0.948. The split-half reliability and stability were 0.671 and 0.703, respectively. The content validity index of the scale was 0.952. The 6-factor structure, supported by the eigenvalues, total variance explained, and scree plot accounted for 71.485 % of the total variance. Moreover, as a result of the confirmatory factor analysis, the average variance extracted values were 0.55 to 0.70, and the model fitting indexes were all in the acceptable range. Conclusions The Chinese version of the Medication Safety Competence Scale had ideal reliability and validity among clinical nurses. The evaluation results of the scale can provide a reference for nursing managers to formulate education plans and intervention measures to improve clinical nurses’ safe medication competence.